Specific clones of Staphylococcus lugdunensis may be associated with colon carcinoma. Issue 1 (January 2018) - Noguchi, Norihisa; Fukuzawa, Mari; Wajima, Takeaki; Yokose, Kaoru; Suzuki, Masae; Nakaminami, Hidemasa; Kawai, Takashi; Moriyasu, Fuminori; Sasatsu, Masanori
Abstract: Staphylococcus lugdunensis produces a tannase with activity that may be associated with the onset of colon carcinoma. To clarify this feature of colon carcinoma-associated S. lugdunensis, we obtained isolates from healthy subjects and patients with colon adenomas and carcinomas and analyzed their genetic backgrounds. In total, 40 S. lugdunensis isolates from 288 rectal swabs collected between 2002 and 2008 were used. These isolates were classified into four groups according to the diseases of the subjects: healthy (n = 13), colon carcinoma (n = 13), colon adenoma (n = 9), and unknown (n = 5). The isolates were also classified by pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing. In addition, an antimicrobial susceptibility test and detection of resistance genes were performed for all isolates. According to the PFGE analysis, 40 isolates could be classified into five groups. Among the groups, carcinoma and colon adenoma patients were significantly more frequently (40.9%) classified into group D ( p <  0.05), whereas healthy subjects were more frequently (38.5%) classified into group A. All isolates in group D were typed as ST27, which was clearly different than isolates in the other groups. All isolates were susceptible to the antimicrobial agents tested, including β-lactams, although seven strains produced β-lactamase. Our data suggest that a specific clone of S. lugdunensis might be associated with colon carcinoma and colon adenoma. This clone showed high susceptibility to many antimicrobial agents. Therefore, eradication therapy may lead to a decreased risk of colon carcinoma.